I knew how it feels but couldn't save my daughter; testimony of an Ethiopian mother on female genital mutilation/cutting - Yohannes Mehretie Adinew; Beza Tamirat Mekete (BMC, 2017)
Abstract Background World Health Organization defines female genital mutilation/cutting as all procedures that involve partial or total removal of the external female genitalia, or other injury to the female genital organs for non-medical reasons. The practice is common in Ethiopia, especially among Somali (99%) ethnic groups. Even though FGM/C is labeled illegal practice according to the revised 2005 Penal Code of the country, the practice is still responsible for misery of many girls in Ethiopia. Methods This personal testimony is presented using woman's own words. Data were collected through in-depth interview with a woman at Gursum health center, Somali regional state, eastern Ethiopia on June 19/2016. The interview was conducted in a private environment and original names were changed to overcome ethical concerns. Informed written consent was obtained from the participant prior to data collection. The interview was audio-taped using a digital voice recorder, later transcribed and translated verbatim from the local language, Amharic to English. Results The study participant described a range of experiences she had during her own and her daughter's circumcision. Three themes emerged from the woman's description: womanhood, social pressure and stigmatization of uncircumcised women and uncertain future. Conclusion Even though the national prevalence may show a decline, FGM/C is still practiced underground. Thus, anti-FGM/C interventions shall take in to account elders influence and incorporate a human rights approach rather than relying merely on the dire health consequences. Further exploration of the determinants of FGM/C on a wider scale is recommended.